Principles of comparative politics - Clark, William Roberts; Golder, Matt; Goldier, Sona Nadenichek (Los Angeles SAGE/CQ Press, 2013)
The groundbreaking first edition of {rinciples of Comparative politics offered the most comprehensive and up-to-date view of the rich world of comparative inquiry, research, and scholarship. Now, thoroughly revised to address the latest developments in the Middle East, the conflict in Somalia, the NATO intervention in Libya and more, the second edition offers students an even better guide to cross-national comparison and why it matters.
pt. 1. What is Comparative Politics? -- pt. 2. The Modern State: Democracy or Dictatorship? -- pt. 3. Varieties of Democracy and Dictatorship -- pt. 4. Varieties of Democracy and Political Outcomes.
Keywords: Comparative government; Democracy; Political science -- Research -- Methodology